Pelatihan Dan Sertifikasi Kompetensi Best Practise Preventive And Predictive Maintenance Pada Dosen Vokasi - Adri Maldi Subardjah; Mokhamad Munir Fahmi; Budi Triyono; Haryadi; Prasetyo; Aris Suryadi; Hanni Maksum Ardi; Dibyo Setiawan (CV. Multi Kreasi Media, 2025)
Training and competency certification are part of efforts to enhance the quality of human resources, particularly vocational lecturers, in mastering best practices in Preventive and Predictive Maintenance. This program was conducted over a period of twelve (12) days and covered both theoretical and practical aspects of Preventive and Predictive Maintenance, including Maintenance Planning & Scheduling, Vibration Analysis, Thermography, and Total Productive Maintenance. The training was organized through a collaboration between the Ministry of Education, Culture, Research and Technology, the Indonesia Endowment Fund for Education (LPDP), and the Indonesian Society of Reliability (ISR). The main objective of this program was to improve lecturers' competencies in Reliability-Centered Maintenance (RCM), Overall Equipment Effectiveness (OEE), failure analysis using methods such as Failure Mode and Effects Analysis (FMEA), Root Cause Analysis (RCA), Root Cause Failure Analysis (RCFA), and Supply Chain Management (SCM). As a result of the training and certification program, all eleven (11) participants were declared certified and received certification from ISR. This achievement serves as capital to support excellent and globally competitive vocational education.